2003
DOI: 10.1065/espr2003.06.155
|View full text |Cite
|
Sign up to set email alerts
|

Practical applications of the fenton reaction to the removal of chlorinated aromatic pollutants

Abstract: In applying practical Fenton-type degradation systems to heavily polluted wastes, either for the pre-treatment of waters with a high COD value prior to biodegradation or for complete mineralization of pollutants, the set up of appropriate reaction conditions appears to be a key factor. Also, it is desirable to keep the concentration of iron salts within the lower limits in order to minimize the production and disposal of iron oxide sludges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In this way, in the anodic oxidation of CMP, the first step was the release of the chloride ion from the aromatic ring to form phenolics or quinones. As for the dechlorination mechanism, in previous studies dealing with other chloro-phenolics, it was usually suggested that the predominant chlorine removal mechanism was the hydroxyl substitution on the phenolic ring structure (ipsosubstitution) [30,48]. Our results were in accordance with this fact, as discussed above.…”
Section: Fate Of the Chlorine In Cmpsupporting
confidence: 95%
“…In this way, in the anodic oxidation of CMP, the first step was the release of the chloride ion from the aromatic ring to form phenolics or quinones. As for the dechlorination mechanism, in previous studies dealing with other chloro-phenolics, it was usually suggested that the predominant chlorine removal mechanism was the hydroxyl substitution on the phenolic ring structure (ipsosubstitution) [30,48]. Our results were in accordance with this fact, as discussed above.…”
Section: Fate Of the Chlorine In Cmpsupporting
confidence: 95%
“…By promoting the formation of OH radicals, either in the subsurface or in pump-and-treat remediation systems, it is possible to convert non-biodegradable xenobiotic compounds into biodegradable compounds (Watts et al, 1999;Teel et al, 2001;Detomaso et al, 2003;Kavitha and Palanivelu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) can be regarded as a potential solution [5,6]. Specifically, Fenton and Fenton-like oxidation are being increasingly used for the abatement of water pollutants [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%